The Efforts of the Madrasah Principal in Preventing Bullying Among Students at MTs NW Aik Bukaq - Siti Ulfa Zuliana; Safinah; Komarudin (Indonesian Journal of Education and Science, 2025)
This research aims to explore and analyze the efforts made by the principal in preventing bullying among students at MTs NW Aik Bukaq. Bullying is a serious issue within educational settings that can negatively impact students’ psychological and social development. As the leader of an educational institution, the principal holds a strategic role in fostering a safe and conducive school environment. This study employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, involving the principal, teachers, and several students as informants. The data analysis was conducted through data reduction, data display, and conclusion drawing. The findings revealed that the principal had implemented various preventive measures to address bullying: (1) anti-bullying policies were established through school regulations; (3) supervision of student interactions within the school environment was strengthened; (3) character development activities were conducted through religious and social programs; and (4) collaboration with guidance and counseling teachers as well as homeroom teachers was established to follow up on potential bullying cases. In addition, the principal applied a persuasive approach toward students with bullying tendencies and maintained intensive communication with parents. These efforts demonstrate the importance of leadership commitment, teacher collaboration, and parental involvement in preventing bullying. The study concludes that comprehensive preventive strategies supported by strong leadership and active stakeholder participation are essential to create a safe and supportive learning environment.